Variable Nutrient Environment Influence on Sweet Sorghum Stalk and Grain Yield - Naik, B. Balaji; Kumar, S. R.; Ramanjaneyulu, A. V. (International Journal of Bio-resource and Stress Management, 2017)
Sweet sorghum is found to be one of the best sources for Ethanol production due to less irrigation requirement and cost of cultivation, at times Indian government had introduced the policy of blending ethanol with petrol and diesel. The present study was aimed to identify suitable sweet sorghum cultivar and quantify the influence of nitrogen and potassium on stalk and grain yield. The results indicated that a significant improvement in total and stripped stalk weight, juice yield, brix value and grain yields were observed with nitrogen fertilization @ 80 kg N ha-1 alone (N1K0). The combined effect of 80 kg N and 40 K2O was found significant on total and stripped stalk weight in 2008 and juice yield in 2009. The cultivar SSV 84 produced higher mean grain yield of 4.01 t ha-1 in 2008 and PAC 52093 with 2.86 t ha-1 in 2009 over CSH 22SS. But this trend was reverse in terms of in total and stripped stalk weight and juice yields. The cultivar CSH 22SS recorded higher brix value (15.4) during drought year 2009 over its preceding wet year 2008. The highest net returns and B:C ratio were recorded with the conjunctive use of N and K2O at their recommended levels during both the years. The cultivars SSV 84 and PAC 52093 were found superior to CSH 22 SS in terms of net returns and B:C ratios during their respective years of study.